Molecular genetic diagnosis of the ‘taxonomically difficult’ Australian endangered orchid, Microtis angusii: an evaluation of the utility of DNA barcoding - Flanagan, Nicola (Universidad de Costa Rica, 2015)
As species are the common currency for conserva- tion efforts, their accurate description is essential for efficient preservation of biological diversity. The use of DNA Barcodes, short DNA sequences that evolve fast enough to differentiate species, has been pro- posed both for the discovery of new species and the identification of previously described species.